Expression of Monocarboxylate Transporter 1 Is Associated With Better Prognosis and Reduced Nodal Metastasis in Pancreatic Ductal Adenocarcinoma. Issue 8 (September 2019) - Sukeda, Aoi; Nakamura, Yuka; Nishida, Yasunori; Kojima, Motohiro; Gotohda, Naoto; Akimoto, Tetsuo; Ochiai, Atsushi
Abstract : Objectives: Because lactate is believed to support tumor growth, monocarboxylate transporters (MCTs), which transport lactate, have been investigated in multiple tumors. However, the significance of MCTs in pancreatic cancer is unclear. Methods: A retrospective survey was conducted on 240 patients who underwent surgical resection for pancreatic ductal adenocarcinoma without preoperative treatment. The expression of MCT1, MCT2, MCT3, MCT4, and the glucose transporter 1 (GLUT1) was assessed in tumor cells and cancer-associated fibroblasts (CAFs) by tissue microarrays and immunohistochemistry. The impact of their expression on patient outcome and clinicopathological characteristics was also analyzed. Results: In tumor cells, MCT1, MCT2, MCT3, MCT4, and GLUT1 were detected in 52 (22%), 31 (13%), 149 (62%), 204 (85%), and 235 (98%) cases, respectively. In CAFs, MCT2, MCT4, and GLUT1 were detected in 9 (3.8%), 178 (74%), and 36 (15%) cases, respectively. In tumor cells, MCT1 expression was associated with extended overall and progression-free survival and decreased nodal metastasis. Conversely, MCT4 expression in CAFs was associated with shortened survival. Conclusions: In tumor cells, MCT1 expression is associated with better prognosis and reduced nodal metastasis in pancreatic cancer, contrary to findings of past in vitro studies. Conversely, MCT4 expression in CAFs is indicative of worse prognosis. Abstract : Supplemental digital content is available in the text.